Pengaruh Keselamatan Kerja dan Kesehatan kerja Terhadap Kinerja Karyawan Unit Finishing PT. Primatexco Indonesia - Farikhul Muafiq; Aghus Jamaluddin Kharis; Aria Mulyapraadana (Pusat Riset dan Inovasi Nasional, 2022)
The occupational safety and occupational health program created by the company in an effort to reduce the number of work accidents that occur when employees work and have an impact on employee performance so that company goals cannot be achieved optimally. Therefore, researchers are interested in studying more deeply and aim to find out how much influence occupational safety and occupational health have on the performance of employees. PT. Primatexco Indonesia. The population of this study was 216 employees and a sample of 68 employees. This research uses a quantitative approach and its analytical techniques, namely double liniear regression analysis. The results of the research obtained occupational safety (X1) has an effect and is significant on employee performance and occupational health (X2) has an effect and is significant on employee performance.